FIP1 Plays an Important Role in Nitrate Signaling and Regulates CIPK8 and CIPK23 Expression in Arabidopsis - Wang, Chao; Zhang, Wenjing; Li, Zehui; Li, Zhen; Bi, Yingjun; Crawford, Nigel M.; Wang, Yong (Frontiers in Plant Science, 2018)
Unraveling the molecular mechanisms of nitrate regulation and deciphering the underlying genetic network is vital for elucidating nitrate uptake and utilization in plants. Such knowledge could lead to the improvement of nitrogen-use efficiency in agriculture. Here, we report that the FIP1 gene (factor interacting with poly(A) polymerase 1) plays an important role in nitrate signaling in Arabidopsis thaliana. FIP1 encodes a putative core component of the polyadenylation factor complex. We found that FIP1 interacts with the cleavage and polyadenylation specificity factor 30-L (CPSF30-L), which is also an essential player in nitrate signaling. The induction of nitrate-responsive genes following nitrate treatment was inhibited in the fip1 mutant. The nitrate content was also reduced in fip1 seedlings due to their decreased nitrate uptake activity. Furthermore, the nitrate content was higher in the roots but lower in the roots of fip1, which may result from the downregulation of NRT1.8 and the upregulation of the nitrate assimilation genes. In addition, qPCR analyses revealed that FIP1 negatively regulated the expression of CIPK8 and CIPK23, two protein kinases involved in nitrate signaling. In the fip1 mutant, the increased expression of CIPK23 may affect nitrate uptake, resulting in its lower nitrate content. Genetic and molecular evidence suggests that FIP1 and CPSF30-L function in the same nitrate-signaling pathway, with FIP1 mediating signaling through its interaction with CPSF30-L and its regulation of CIPK8 and CIPK23. Analysis of the 3’-UTR of NRT1.1 showed that the pattern of polyadenylation sites was altered in the fip1 mutant. These findings add a novel component to the nitrate regulation network and enhance our understanding of the underlying mechanisms for nitrate signaling.